Optimizing antibiotic duration and percutaneous nephrostomy timing in urosepsis complicated by upper ureteral stones: a retrospective study - Jen-Ting Hsu; Chia-Min Lin; Shun-Fa Hung; Shiu-Dong Chung; Pai‑Yu Cheng (BMC Urology)
Abstract Background Urosepsis is a potentially life-threatening condition caused by urinary tract infections and is usually associated with urolithiasis-induced obstruction. No established guidelines exist regarding the optimal timing of antibiotic administration, appropriate duration of urinary drainage, or scheduling of definitive ureteroscopic lithotripsy (URSL) in patients with urolithiasis-induced obstructive acute pyelonephritis (APN). Therefore, this study aimed to investigate the key factors influencing the management of urosepsis secondary to upper ureteral stones, specifically focusing on the optimal duration of antibiotic therapy, risk factors for post-URSL fever, and timing of percutaneous nephrostomy (PCN) drainage to improve clinical outcomes. Methods This retrospective study included 107 patients with urolithiasis-induced obstructive APN complicated by urosepsis who underwent treatment between 2013 and 2019. These patients underwent PCN drainage, followed by URSL. Data on patient demographics, comorbidities, laboratory results, microbiological cultures, and stone characteristics were obtained and analyzed. Results Among the 107 patients, 34 (32%) had post-URSL fever. The afebrile group received longer antibiotic therapy (7.1 vs. 5.7 days, p = 0.022) and had shorter postoperative hospital stays (3.1 vs. 5.3 days, p = 0.015). Logistic regression analysis showed that antibiotic duration and the interval from PCN to URSL were significant predictors of fever. Diabetes mellitus was a significant risk factor for post-URSL fever in patients treated with antibiotics for more than 7 days (odds ratio = 9.07, p = 0.03). Emergent PCN insertion was associated with earlier URSL and a shorter hospital stay. Conclusions This study emphasizes the importance of determining the optimal duration of antibiotic therapy before URSL in patients with urosepsis complicated by upper ureteral stones. Post-URSL fever correlates with a shorter duration of antibiotic therapy, and emergent PCN insertion results in earlier URSL and a shorter hospital stay. Diabetes mellitus significantly predicted post-URSL fever.